2015
DOI: 10.1136/bmjopen-2015-008800
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of advance care planning in elderly Italian and Greek speaking patients as compared to English-speaking patients: an Australian cross-sectional study

Abstract: ObjectivesTo assess the feasibility and acceptability of facilitated advance care planning (ACP) discussions in elderly Italian and Greek-speaking inpatients compared to English-speaking inpatients.Design, setting and participantsThis cross-sectional study with convenience sampling was conducted in Melbourne, Australia, and recruited hospital inpatients with medical decision-making capacity, aged 65 years or above, who spoke Greek (25 patients), Italian (24 patients) or English (63 patients).InterventionFacili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Absence of privacy is a barrier to ACP in hospital 33. The use of an interpreter is an important facilitator in patients from a non-English-speaking background 40. ACP documents made prior to admission are often not available or identified during an admission 30…”
Section: Resultsmentioning
confidence: 99%
“…Absence of privacy is a barrier to ACP in hospital 33. The use of an interpreter is an important facilitator in patients from a non-English-speaking background 40. ACP documents made prior to admission are often not available or identified during an admission 30…”
Section: Resultsmentioning
confidence: 99%
“…Detering et al. () demonstrated that when these logistical barriers were overcome through provision of interpreter services and in‐language information, ACP outcomes with Greek and Italian patients were similar to English‐speaking patients (Detering et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, other logistical barriers may be just as important, for instance language and the ability to obtain and comprehend information related to health (Con, 2007;Shaw, Zou, & Butow, 2015;Yonashiro-Cho, Cote, & Enguidanos, 2016). Detering et al (2015) demonstrated that when these logistical barriers were overcome through provision of interpreter services and in-language information, ACP outcomes with Greek and Italian patients were similar to Englishspeaking patients (Detering et al, 2015).…”
mentioning
confidence: 99%
“…35,36 Nevertheless, the prevalence of ADs in Swiss terminal cancer patients remains low (29%), 37 revealing the lack of advance care planning concepts in Switzerland. This is different from other countries, 38,39 where discussions about advance care planning are part of routine health care.…”
Section: Ads: Medical Representativementioning
confidence: 60%